Social Enterprises in Rural Areas: A Comparative Study of the Baltic States - Evans, Roger; Raudsaar, Mervi; Līcīte-Ķurbe, Lāsma; Butkevičienė, Eglė; Erpf, Philipp; Urmanavičienė, Audronė; Raišienė, Agota Giedrė (Social Enterprise in Central and Eastern Europe, 2021)
This chapter provides information about the earlier issues by presenting a cross-case analysis of rural social enterprises from Latvia, Lithuania and Estonia. Social enterprises seek to produce goods and services with a social or environmental purpose, and they pursue the general interest of local communities, people and/or social groups. The orientation towards the public good does not imply that social enterprises do not undertake strategies to achieve economic and financial efficiency; on the contrary, they must constantly create economic value to guarantee their survival over time. The successful operation of rural social enterprises is highly dependent on their relationships with their stakeholders. Many interest groups can indeed be involved in social enterprises; they can be divided into external stakeholders and internal stakeholders. Rural emigration and migration to cities is a major issue in the three countries, following the economic and social changes of the 1990s.